Korelasi Higher Criticisim atas Inerrancy Alkitab bagi Iman Kristen - Halawa, Iman Kristina; Purwonugroho, Daniel Pesah (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
This article is composed to explore the meaning of higher criticism concerning the inerrancy of the Bible and its impact on the Christian faith. The Bible as the word of God is a core doctrine in the Christian faith that cannot be negotiated. When reading the Bible, readers must submit themselves to the system of biblical understanding. Reading the Bible and subsequently engaging in textual criticism of the Bible is considered an incorrect approach. Criticism of the Bible, whether textual or historical criticism, began to particularly develop during the Enlightenment era. Biblical inerrancy is a statement asserting that the Bible is without error. The relationship between biblical inerrancy and biblical criticism is dialectical in nature. The author employs a descriptive qualitative research method to demonstrate that the Bible possesses the attribute of inerrancy, is a revelation from God, and to conduct exegetical studies from both the Old and New Testaments to provide authentic evidence for the strengthening of the Christian faith.